2009
DOI: 10.1021/es901357u
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Hydroxylated Brominated Diphenyl Ethers: Natural Compounds or Man-Made Flame Retardants?

Abstract: Polybrominated diphenyl ethers (PBDEs) have been widely used as flame retardants. The structurally related hydroxylated PBDEs (OH-PBDEs) and methoxylated PBDEs (MeO-PBDEs) occur in precipitation, surface water, wildlife, and humans. The formation of OH-PBDEs in wildlife and humans is of considerable concern due to their greater toxicities relative to PBDEs and MeO-PBDEs. Research to date suggests that OH-PBDEs are formed by hydroxylation of PBDEs, and MeO-PBDEs are then formed by methylation of the OH-PBDEs. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
231
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(251 citation statements)
references
References 41 publications
18
231
1
1
Order By: Relevance
“…Hence, OH-BDEs are unlikely to originate from the anthropogenic PBDEs. Detectable contents of MeO-BDEs were not observed in controlled exposure studies (McKinney et al, 2006;Wan et al, 2010bWan et al, , 2009Zhang et al, 2010), and thus MeO-BDEs are expected to be natural compounds.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hence, OH-BDEs are unlikely to originate from the anthropogenic PBDEs. Detectable contents of MeO-BDEs were not observed in controlled exposure studies (McKinney et al, 2006;Wan et al, 2010bWan et al, , 2009Zhang et al, 2010), and thus MeO-BDEs are expected to be natural compounds.…”
Section: Introductionmentioning
confidence: 94%
“…These compounds were initially considered as metabolites or by-products of anthropogenic PBDEs because of the similarities in their structure (Haglund et al, 1997;Marsh et al, 2006). Some in vivo and in vitro studies have reported the biotransformation of OH-BDEs from various PBDEs (Erratico et al, 2010;Hakk et al, 2009;Malmberg et al, 2005;Qiu et al, 2007;Stapleton et al, 2009) despite the absence of OH-BDE formation in other PBDE exposure experiments (Benedict et al, 2007;Browne et al, 2009;Stapleton et al, 2006;Wan et al, 2009). However, concentrations of detected OH-BDEs were markedly lower than PBDEs, with a conversion ratio of w3% (Erratico et al, 2010;Hamers et al, 2008;Malmberg et al, 2005;Stapleton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a considerable interest in determining the sources and relationships among PBDEs, OHPBDEs and MeO-PBDEs. 6-MeO-BDE-47, 2 0 -MeO-BDE-68, 6-OH-BDE-47, and 2 0 -OH-BDE-68 were the dominant MeO-PBDEs and OH-PBDEs found in marine organisms (Kelly et al, 2008;McKinney et al, 2006;Verreault et al, 2005;Wan et al, 2009). These orthosubstituted OH-PBDEs and MeO-PBDEs have been structurally identified and confirmed as natural compounds (Malmvarn et al, 2005(Malmvarn et al, , 2008.…”
Section: Introductionmentioning
confidence: 96%
“…4,5 The source of the OH-PBDE metabolites and MeO-PBDE analogues can be either intake from marine food or metabolically derived biotransformation of PBDEs by humans themselves. 6 Because of their persistence in the environment and bio-accumulation in the food chain, even low levels of PBDEs might pose great risk to human health. 7 Over the past few years, increasing evidence has become available that exposure to PBDEs might result in many health hazards such as disruption of endocrine system, 8 developmental neurotoxicity, 9 decreased female fecundability, 10 and even cancer.…”
Section: Introductionmentioning
confidence: 99%